Artificial Intelligence in Higher Education 2022
DOI: 10.1201/9781003184157-9
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Based Tools in Research Writing

Abstract: The global adoption of technology in education is transforming the way we teach and learn. Artificial Intelligence is one of the disruptive techniques to customise the experience of different learning groups, teachers, and tutors. This book offers knowledge in intelligent teaching/learning systems, and advances in e-learning and assessment systems. Features include:• Highlights the broad field of AI applications in education, regarding any type of Artificial Intelligence that is correlated with education. • Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…A number of other limitations with ChatGPT are explained on the company's website (OpenAI, 2022). However, it is likely in the future that other natural language applications of AI will be developed that will be able to quickly scan the Internet and trawl thousands of openly available scientific articles on different topics to generate a written response with appropriate forms of referencing within milliseconds (Adams & Chuah, 2022). This could have far reaching implications for nursing education.…”
Section: Editorialmentioning
confidence: 99%
“…A number of other limitations with ChatGPT are explained on the company's website (OpenAI, 2022). However, it is likely in the future that other natural language applications of AI will be developed that will be able to quickly scan the Internet and trawl thousands of openly available scientific articles on different topics to generate a written response with appropriate forms of referencing within milliseconds (Adams & Chuah, 2022). This could have far reaching implications for nursing education.…”
Section: Editorialmentioning
confidence: 99%
“…Lütge et al [115] presented a similar proposal in which they suggested teaching global citizenship through foreign language education in order to "empower educational actors to orient themselves in the face of unknowns" [116, p. 2]. As AI-enhanced writing tools become more available to second language learners, foreign language teachers will have to find different ways to reward creativity and value the freedom of the learners [12,13]. They will also have to make use of these tools in reducing their workload by getting these systems to highlight students' errors and writing problems.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why Scopus was chosen over other scholarly databases was that it is considered the largest and most comprehensive database for peer-reviewed abstract and citation literature [11]. Based on relevant AI-powered writing assistance literature [12,13], we identified a number of search keywords (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Rewriting, summarizing, and abbreviating the text make our writing easy for readers to read. According to Adams & Chuah (2022), studies examine QuillBot's effectiveness and usefulness for writers and researchers.…”
Section: Discussionmentioning
confidence: 99%